A model study of cooperative binding of ionic surfactants to oppositely charged flexible polyions - Nishio, T.; Shimizu, T.; Yoshida, Sh.; Minakata, A. (Condensed Matter Physics, 2014)
A novel statistical model for the cooperative binding of monomeric ligands to a linear lattice is developed to study the interaction of ionic surfactant molecules with flexible polyion chain in dilute solution. Electrostatic binding of a ligand to a site on the polyion and hydrophobic associations between the neighboring bound ligands are assumed to be stochastic processes. Ligand association separated by several lattice points within defined width is introduced for the flexible polyion. Model calculations by the Monte Carlo method are carried out to investigate the binding behavior. The hypothesis on the ligand association and its width on the chain are of importance in determining critical aggregation concentration and binding isotherm. The results are reasonable for the interpretations of several surfactant-flexible polyion binding experiments. The implications of the approach are presented and discussed. Для вивчення взаємодiї молекул iонного сурфактанта з гнучким полiiонним ланцюжком у розведеному розчинi запропоновано нову статистичну модель для колективного зв’язування мономерних лiганд
з лiнiйною граткою. Припускається, що електростатичне зв’язування лiганди з вузлом на полiiонi та гiдрофобнi зв’язки мiж сусiднiмi зв’язаними лiгандами є стохастичними процесами. Для гнучкого полiiона
вводиться асоцiацiя лiганд, вiдокремлених декiлькома гратковими точками в межах визначеної ширини.
Для того, щоб дослiдити поведiнку зв’язування, здiйсноються обчислення методом Монте Карло. Гiпотеза
асоцiацiї лiганди та її ширини на ланцюжку є важливою для визначення критичної концентрацiї агрегацiї
та iзотерми зв’язування. Результати є прийнятними для iнтерпретицiї декiлькох експериментiв по зв’язуванню сурфактант-гнучкий полiiон. Представлено та обговорено застосування методу.